Immunological efficacy of Vaccination against Measles in Children with Down syndrome - S. P. Kaplina; S. M. Kharit; E. I. Alexandrova (Журнал инфектологии, 2014)
The data of current vaccination process of cellular, humoral immunity and specific antibody formation in 41 children with Down syndrome at the age of 1 year to 6 years old is observed. To prevent easles used measles vaccine (n=12), divaccine -measles-mumps (n=21) and or Priorix vaccine (n=8). The comparison group consisted of 63 children without Down syndrome. The post-vaccination period in 97,6% of children with Down syndrome cases are asymptomatic, only 2,4% of children mentioned layering of intercurrent diseases. The immunological status in children with Down syndrome is characterized by a significant decrease in the  umber leucocytes, lymphocytes, CD3+, CD4+, CD8+ and absolute number of CD20+, but functional activity of the cells is preserved. By 30 days after immunization they have increased leucocytes, lymphocytes, CD 95+cells. The number of antibodies significantly increased (6,63±0,33 compared to 5,79±0,32 log2, р < 0,05).